A Survey of Hesitancy and Response to the COVID-19 Vaccine Among Patients With Epilepsy in Northeast China - Li, Nan; Chu, Chaojia; Lin, Weihong (Frontiers in Neurology, 2021)
Objective: This study was conducted to investigate the hesitancy and response of people with epilepsy (PWE) to the COVID-19 vaccine. Methods: We conducted an online survey among PWE in northeast China about hesitancy and response to the COVID-19 vaccine. Their demographic background and symptomatic data about epilepsy were also recorded, and we analyzed the epilepsy-related risk factors for delaying the vaccine. Results: In total, 357 patients with confirmed epilepsy were included in the survey, and only 38 (11%) patients received the COVID-19 vaccine. Fear of aggravating epilepsy (58%, n=185), discouragement from health workers for epilepsy (22%, n=70) and patients’ fear of other unknown serious side effects (13%, n=42) were the main reasons for delaying vaccination. A higher seizure frequency was the only epilepsy-related risk factor for delaying the vaccine (OR = 1.104, 95% CI: 0.988–1.233). None of the vaccinated patients reported that the vaccine aggravated their epilepsy. Significance: Understanding concerns about the COVID-19 vaccine among PWE could help to improve health education and promote the establishment of an immune barrier.